Deuterium retention and thermal conductivity in ion-beam displacement-damaged tungsten. (August 2017) - Tynan, G.R.; Doerner, R.P.; Barton, J.; Chen, R.; Cui, S.; Simmonds, M.; Wang, Y.; Weaver, J.S.; Mara, N.; Pathak, S.
Highlights: Paper presents fuel retention and thermo-mechanical property evolution in ITER-grade W samples exposed to DEMO/FNSF relevant ion fluxes, fluences and damage levels across a range of temperatures. Damaging temperature and damage levels are independently controlled, and plasma D ion implantation is carried out at low temperature to decorate damage sites with trapped D. Retained inventory is then measured with NRA and TDS. A pronounced (5.5x) increase in retained D inventory for 0.2 dpa damage levels applied at low temperatures (< 500 K). Retention increases weaker than linearly with dpa. Detrapping and release of increased retention inventory occurs at release temperatures of 700–900 K. Retained inventory drops for damaging temperatures above 500 K and returns to undamaged levels for damaging temperatures of 1200 K, indicating that annealing can overcome ion-beam damage rates. Retention changes are large enough to impact tritium breeding and inventory in DEMO/FNSF like devices. Significant increases (>2x) in indentation yield stress is observed. A pronounced (>3x) decrease in thermal conductivity occurs in the damaged layer. If such a change occurred across a wide zone in neutron damaged material, it would have a pronounced impact on divertor target performance. Abstract: Retention of plasma-implanted D is studied in W targets damaged by a Cu ion beam at up to 0.2 dpa with sample temperatures between 300 K and 1200 K. At a D plasma ion fluence of 10 24 /m 2 on samples damaged to 0.2 dpa at 300 K, the retained D retention inventory is 4.6 × 10 20 D/m 2, about ∼5.5 times higher than in undamaged samples. The retained inventory drops to 9 × 10 19 D/m 2 for samples damaged to 0.2 dpa at 1000 K, consistent with onset of vacancy annealing at a rate sufficient to overcome the elevated rate of ion beam damage; at a damage temperature of 1200 K retention is nearly equal to values seen in undamaged materials. A nano-scale technique provides thermal conductivity measurements from the Cu-ion beam displacement damaged region. We find the thermal conductivity of W damaged to 0.2 dpa at room temperature drops from the un-irradiated value of 182 ± 3.3 W/m K to 53 ± 8 W/m K.